Androgen and Luteinizing Hormone Stimulate the Function of Rat Immature Leydig Cells Through Different Transcription Signals - Li, Xiaoheng; Zhu, Qiqi; Wen, Zina; Yuan, Kaimin; Su, Zhijian; Wang, Yiyan; Zhong, Ying; Ge, Ren-Shan (Frontiers in Endocrinology, 2021)
The function of immature Leydig cells is regulated by hormones, such as androgen and luteinizing hormone (LH). However, the regulation of this process is still unclear. The objective of this study was to determine whether luteinizing hormone (LH) or androgens contribute to this process. Immature Leydig cells were purified from 35-day-old male Sprague Dawley rats and cultured with LH (1 ng/ml) or androgen (7α-methyl-19- nortestosterone, MENT, 100 nM) for 2 days. LH or MENT treatment significantly increased the androgens produced by immature Leydig cells in rats. Microarray and qPCR and enzymatic tests showed that LH up-regulated the expression of Scarb1, Cyp11a1, Cyp17a1, and Srd5a1 while down-regulated the expression of Sult2a1 and Akr1c14. On the contrary, the expression of Cyp17a1 was up-regulated by MENT. LH and MENT regulate Leydig cell function through different sets of transcription factors. We conclude that LH and androgens participate in the regulation of rat immature Leydig cell function through different transcriptional pathways.